Corporate Governance and earnings management in brazilian financial institutions - Souza, Paulo Vitor Souza de; Araújo, Ana Gabriela de Souza; Neves, Raquel Bandeira (Revista de Administração da UFSM, 2023)
Purpose: This study aimed to verify how corporate governance measures relate to earnings management in Brazilian publicly traded financial institutions. Design/methodology/approach: To carry out the research, 20 financial institutions listed on B3 were analyzed, with annual data from 2010 to 2019 obtained from the websites of the Brazilian Securities and Exchange Commission (CVM) and the IF.Data of the Central Bank of Brazil (Bacen). To obtain the results, regression models were estimated for each attribute of corporate governance in comparison with the selected earnings management measure. Findings: The results point to several associations of corporate governance attributes with earnings management measures. That is, corporate governance attributes reduce/increase earnings management in financial entities. Research limitations/implications: The findings of this study aim to assist company managers in improving their corporate governance policies to reduce accounting choices related to accounting management. Originality/value: The study proves to be original by the use of a broad panorama referring to corporate governance measures. Generally, studies that analyze the effects of governance on earnings management use few measures for this attribute. The study also advances by specifically analyzing financial institutions, generally excluded from studies on information quality due to their particularities.